Doing art history in the digital age. (January 2022) - Sonal
Abstract : This paper explores the dimensions of visual history in the digital age. Do digital repositories offer newer paradigms in art historical research? At the most elementary level, it can be easily said that digital tools do allow for closer scrutiny and analysis of art objects with respect to its material composition. A deeper question that needs to be explored is whether the digital age allows for newer theoretical approaches to doing art history. As inventories, museums, art galleries and libraries have been digitizing their collections, there has been a definite shift in the ways of seeing art objects due to the comfort and ease of digital devices. Given the fact that artifacts have a historical process of conceptualization, production, circulation and reception, historical art objects can be seen as a unique entry point into the larger global history of circulation of art works right from the time of their initial production to their later reproduction in print and finally to the times of digitization.